A review on the global widespread of TTV infection among humans population - Jarkasi, Nur Syazwani; Sekawi, Zamberi; Cheah, Yoke Kqueen; Othman, Zulkefley (Universiti Putra Malaysia Press, 2018)
Torque Teno Virus (TTV) is a human-infected virus that is present ubiquitously in nature. Globally, it infects up to 95% of the healthy individuals without any clinical manifestations. The widely used laboratory diagnosis of TTV infection is Polymerase chain reaction (PCR). Nevertheless, several other methods have been developed. The rapid growth of TTV variants over time has posed a challenge in estimating the global TTV infection as none of the PCR protocol has the ability to detect the entire spectrum of TTV variants. Multiple TTV epidemiological studies have been conducted among Asian population, whereas other continents showed a limited number of studies. The horizontal and vertical transmission of TTV among humans population, as well as interspecies transmission are potentially related to the global widespread of TTV infection.